Annie's song eaudiobook - Anderson, Catherine (Tantor Media, 2020)
A classic Catherine Anderson romance filled with hope. Annie Trimble lives in her own world. Shunned by the town for being a simpleton, Annie is kept close to home by her parents. She enjoys her freedom roaming the woods and befriending wild creatures. Frequently taunted by children and adults, Annie's world is shattered when one man takes the torment too far. Shocked by his brother's cruelty toward the girl, Alex Montgomery will do whatever it takes to make amends—even when it means marrying Annie. Soon Alex is charmed by her childlike innocence and begins to realize that the beautiful young woman is not as slow-witted as everyone believes. As Alex falls deeper in love, he becomes more determined to break through Annie's wall of silence.